Control of Bacillus subtilis cell shape by RodZ. (23rd July 2013) - Muchová, Katarína; Chromiková, Zuzana; Barák, Imrich; Vicente, Miguel; Ayala, Juan; Daley, Daniel
Summary The bacterial cell wall ensures the structural integrity of the cell and is the main determinant of cell shape. In Bacillus subtilis, three cytoskeletal proteins, MreB, MreBH and Mbl, are thought to play a crucial role in maintaining the rod cell shape. These proteins are thought to be linked with the transmembrane proteins MreC, MreD and RodA, the peptidoglycan hydrolases, and the penicillin‐binding proteins that are essential for peptidoglycan elongation. Recently, a well‐conserved membrane protein RodZ was discovered in most Gram‐negative and Gram‐positive bacteria. This protein seems to be an additional member of the elongation complex. Here, we examine the role of RodZ in B. subtilis cells. Our results indicate that RodZ is an essential protein and that downregulation of RodZ expression causes the formation of shorter and rounder cells. We also found a direct interaction between RodZ and the cytoskeletal and morphogenetic proteins MreB, MreBH, Mbl and MreD. Taken together, we demonstrated that RodZ is an important part of the cell shape determining network in B. subtilis.